Shadows of a Sunbelt City : The Environment, Racism, and the Knowledge Economy in Austin - Tretter, Eliot (Book collections on Project MUSE., 2016)
"Austin, Texas is generally depicted as one of the great urban success stories of the past half century--a place that has grown enormously through 'creative class' strategies that emphasize diversity and environmental consciousness. Eliot Tretter's book reinterprets this familiar story by exploring the racial and environmental underpinnings of the postindustrial knowledge economy. He is particularly attentive to the role of the University of Texas (often working with federal, municipal, and private-sector partners), and the book will join a growing critical literature about how universities shape urban environments"--Provided by publisher.